On Gruss Type Integral Inequality Involving the Saigo's Fractional Integral Operators - (:unkn) unknown (EUDOXUS PRESS, LLC, 2015)
Using Saigo's fractional integral operators, we establish a generalized version of the Gruss type integral inequality related to the bounded integrable functions, whose bounds are integrable functions. Some special cases of our results are also considered.
Keywords: Gruss integral inequalities; Gauss hypergeometric function; fractional integral operators; MONOTONE ITERATIVE TECHNIQUE; DIFFERENTIAL-EQUATIONS; IMPROVEMENT